2021
DOI: 10.1111/mpp.13091
|View full text |Cite
|
Sign up to set email alerts
|

ARGONAUTE 2 increases rice susceptibility to rice black‐streaked dwarf virus infection by epigenetically regulating HEXOKINASE 1 expression

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Constant induction of AtHXK1 and 2 transcripts in Arabidopsis resulted in elevated resistance to the infections of necrotrophic fungi ( Alternaria brassicicola ) and bacterial P. syringae , indicating the defense and immunity roles of HXK against various pathogens [ 40 , 46 ]. The underlying mechanisms of HXK involved in regulating immunity and defense appeared to be related to altered ROS accumulation, further supported by several recent works performed on rice and apples [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Constant induction of AtHXK1 and 2 transcripts in Arabidopsis resulted in elevated resistance to the infections of necrotrophic fungi ( Alternaria brassicicola ) and bacterial P. syringae , indicating the defense and immunity roles of HXK against various pathogens [ 40 , 46 ]. The underlying mechanisms of HXK involved in regulating immunity and defense appeared to be related to altered ROS accumulation, further supported by several recent works performed on rice and apples [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 53%
“…tomato DC3000 through the glucose effect mediated by AtHXK1-related pathways [ 46 ]. Overexpression of native OsHXK1 in rice led to improved ROS accumulation and leaf resistance to virus infection [ 47 ]. Moreover, a recent report demonstrated that constant induction of MdHXK1 expression in apple ( Malus domestica ) enhanced resistance to ring rot fungi pathogen and ROS production related to glucose signaling [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein in each sample was separated in sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS‐PAGE) gels through electrophoresis and then transferred onto polyvinylidene fluoride (PVDF) membranes. Antibody against FLAG was purchased from Sigma‐Aldrich (Wang et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A rice LRR receptor-like protein and its adaptor kinase SOBIR1 were reported to be involved in immunity against RBSDV infection [ 13 ]. Rice ARGONAUTE (AGO) proteins play crucial roles in plant defense against RBSDV invasion by regulating HEXOKINASE 1 expression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%